The Effect of Noise Exposure on Hearing Function and Vestibular Evoked Myogenic Potentials - Ozgenur Cetinbag-Kuzu; Hande Bahadir; Enis Alpin Guneri; Arif Hikmet Cimrin; Gunay Kirkim (Noise and Health, 2023)
Purpose: Exposure to noise can cause damage to both auditory and vestibular systems. The objective of this study is to evaluate how noise exposure affects the hearing and vestibular systems in individuals with noise-induced hearing loss (NIHL). Methods: This study included 80 subjects (40 subjects with NIHL, and 40 controls), between 26 and 59 years old. For hearing assessment, pure-tone audiometry, extended high-frequency audiometry, tympanometry, acoustic reflex threshold, and distortion product otoacoustic emission tests were used; for vestibular assessment, the cervical and ocular vestibular evoked myogenic potentials tests were used. Results: Statistically significant differences were found between the two groups in 3 to 6 kHz frequency thresholds; in extended high-frequency audiometry tests, there were also significant differences between groups at all frequencies from 9.5 to 16 kHz. The cervical and ocular vestibular evoked myogenic potentials thresholds were significantly higher and N1-P1 amplitudes were significantly lower in the NIHL group. Conclusion: Noise can lead to damage to both auditory and vestibular functions. Therefore, audiological assessments and vestibular evoked myogenic potentials could be clinically useful for examining patients with NIHL.